(untitled) - Bisson, T. A. (New York, 1939)
This book introduce the manchurian crisis 1931 - 1933. Japanese pressure on resurgent China 1933 - 1937. Collapse of naval limitation. Japanese - American trade friction 1933 - 1936...
Keywords: Hoa Kỳ,United States; Quan hệ ngoại giao,Foreign relations; 1933-1945,1933-1945